2020
DOI: 10.21203/rs.3.rs-117230/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender and Socioeconomic Disparities in Reasons for Not Smoking Cigarettes Among Danish Adolescents

Abstract: Objective: To examine gender and socioeconomic differences in adolescents’ reasons for not smoking cigarettes using self-reported data from Danish 14-year-olds (N = 1,559) collected in 2018. χ2-tests were used to assess whether the proportion of students who rated 12 statements as important reasons for not smoking cigarettes differed according to gender and family occupational social class (OSC).Results: More girls than boys stated that thinking the taste of cigarettes is disgusting, not being allowed to smoke… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Despite the stigmatization of female smoking in the Middle East, girls associate this behavior with masculinity; they see smoking as an act of rebellion against gender discrimination in the family and society 35 . Gender also affects the adoption of preventive smoking initiatives 36 . Accordingly, no supporting evidence has been reported for the effectiveness of gender‐nonspecific antismoking programs on girls 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the stigmatization of female smoking in the Middle East, girls associate this behavior with masculinity; they see smoking as an act of rebellion against gender discrimination in the family and society 35 . Gender also affects the adoption of preventive smoking initiatives 36 . Accordingly, no supporting evidence has been reported for the effectiveness of gender‐nonspecific antismoking programs on girls 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, research indicates that girls are more positive about several components of smoking prevention interventions ( Lund et al, 2020 ). Further, more girls than boys reported that health dangers, the risk of getting addicted, not being allowed to smoke by parents, and the fact that smoking is illegal until the age of 18 were important reasons not to smoke cigarettes ( Kjeld et al, 2021 ). Thus, there seem to be gender differences in both the perception of and engagement in risk behaviours.…”
Section: Discussionmentioning
confidence: 99%